Organoleptic Test on Fresh Cheese and Papain Enzyme Rennet Coagulant from Goat's Milk Based on Storage Time - Wangi, Asri (Jurnal Peternakan Integratif, 2021)
Innovations in milk processing include making it into fresh cheese using local coagulant. Â This study aims to determine the effect of papain enzyme levels on the coagulation process of milk formaking fresh cheese. This research method used a 4 x 4 factorial completely randomized design with 2 replications of factor A giving papain enzyme levels, namely A0 = 0.2 g (using commercial rennet), A1 = 0.1 g papain enzyme rennet, A2 = 0.2 g papain enzyme rennet, A3 = 0.3 g papain enzyme rennet, and factor B storage time B0 = 0 days B1 = 5 days B2 = 10 days and B3 = 15 days. The variables measured were organoleptic tests including color, aroma, and preference. Based on the results of the study, it was found that from the addition of four levels of papain enzyme used and four variations of storage time, the administration of papain enzyme 0.3 g (A3) and storage time of 15 days (B3) was the optimal treatment to increase color, aroma, and preference for cheese and can be used as an alternative to the use of rennet